Syntaktische Exponenten der Lexeme - Darski, Józef Paweł (Studia Germanica Posnaniensia, 2018)
The author rejects the terms of traditional grammar: "the case ending" and "personal ending" because of their inadequacy and suggests the substitution of these terms with a new term "syntactic index". Restricting himself to the examples from Polish and German the author comes to the definition of syntactic index through the analysis of word forms of the same lexeme. The definition is much general that it may be applied to languages of various types.